Analisis Debit Banjir Rencana Sungai Talangsari Kota Samarinda: (Studi Kasus, Sungai Talangsari, Desa Gunung Lingai, Kecamatan Sungai Pinang, Kota Samarinda) - Bakri, Muh. Yusuf; Assiddieq, Moch; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2025)
Flood discharge design analysis is an important step in water resources planning and management, especially for flood risk mitigation in areas prone to inundation. This study aims to calculate the flood discharge design in the Talangsari River Basin using appropriate hydrological methods, namely the Log Person Type III distribution method, the Rational Method and the Manning Formula Method. The annual maximum rainfall data from the Web. BPS Samarinda City for 11 years has been used as the basis for analysis. The analysis process involves calculating rainfall intensity, watershed area, and runoff coefficient to obtain the flood discharge design with various periods of years 2, 5, 10, 25, 50, and 100. The results of the analysis show that the flood discharge increases as the period increases, with a maximum discharge of 9,429 m³/s for the year period. These results provide an important reference for flood control infrastructure planning, such as river widening, reducing riverbed sediment and strengthening riverbanks using crushed stone foundations, to minimize the impact of losses due to flooding in the future.